Technological Learning, Energy Efficiency, and CO2 Emissions in China's Energy Intensive Industries - Rock, Michael T.; Toman, Michael; Cui, Yuanshang; Jiang, Kejun; Song, Yun; Wang, Yanjia (World Bank, Washington, DC, 2013)
Since the onset of economic reforms in 1978, China has been remarkably successful in reducing the carbon dioxide intensities of gross domestic product and industrial production. Most analysts correctly attribute the rapid decline in the carbon dioxide intensity of industrial production to rising energy prices, increased openness to trade and investment, increased competition, and technological change. China's industrial and technology policies also have contributed to lower carbon dioxide intensities, by transforming industrial structure and improving enterprise level technological capabilities. Case studies of four energy intensive industries -- aluminum, cement, iron and steel, and paper -- show how the changes have put these industries on substantially lower carbon dioxide emissions trajectories. Although the changes have not led to absolute declines in carbon dioxide emissions, they have substantially weakened the link between industry growth and carbon dioxide emissions.